2010
DOI: 10.1055/s-0029-1240626
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance of Mitroflow Aortic Pericardial Bioprosthesis – Optimizing Management for the Small Aortic Annulus

Abstract: The IN VIVO effective orifice areas by valve size of the Mitroflow aortic pericardial bioprosthesis provide the opportunity of avoiding obstructive characteristics for all valve sizes, including optimizing the management of the small aortic annulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
4
25
2
Order By: Relevance
“…8 In this issue of Circulation, Sénage et al 9 strike a note of warning against the use of the Mitroflow aortic valve. Some of the previous reports have shown 99% 5-year freedom from SVD in Mitroflow valve, 6,10 but in this report, the 5-year freedom from SVD was 91.6% and, when a 19-mm Mitroflow was used, 79.8%. The follow-up time was short (3.8±2.0 years), but the first SVD was observed only 14 months after implantation.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…8 In this issue of Circulation, Sénage et al 9 strike a note of warning against the use of the Mitroflow aortic valve. Some of the previous reports have shown 99% 5-year freedom from SVD in Mitroflow valve, 6,10 but in this report, the 5-year freedom from SVD was 91.6% and, when a 19-mm Mitroflow was used, 79.8%. The follow-up time was short (3.8±2.0 years), but the first SVD was observed only 14 months after implantation.…”
contrasting
confidence: 70%
“…The valve is placed in the supra-annular position compared with the intra-annular position in some of the other bioprostheses. These characteristics allow superior valve hemodynamics in the Mitroflow aortic valve, especially in those with a small aortic annulus (19 and 21 mm) 6 ; therefore, the Mitroflow aortic valve is considered an ideal valve for patients with a small aortic root.…”
mentioning
confidence: 99%
“…The only other prosthesis with an externally mounted section of pericardium is the Mitroflow prosthesis, which has been reported to have excellent hemodynamic performance. 24, 25 Only a few studies have evaluated the hemodynamic performance of the Trifecta valve, 6-9 and only one study has directly compared postoperative hemodynamic performance of the Trifecta valve with a conventional prosthetic valve in clinical practice. 6 In that study, Wendt et al reported no significant difference in MPG or EOA at discharge between the Trifecta and Magna valves, although the Trifecta had a larger EOA at 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The valve stent frames are composed of Elgiloy, a corrosion-resistant cobalt-chromium spring alloy [13,14]. The Mitroflow W (Sorin Group, Milano, Italy) is composed of a polymer stent covered with a polyester cloth, while the leaflets are made from a single sheet of bovine pericardium mounted on the outside of the stent [15,16]. We studied sizes 19 and 25.…”
Section: Bioprosthesesmentioning
confidence: 99%
“…All the investigated prosthetic types are in clinical use for aortic valve replacement and are regarded as MRI-safe. Their hemodynamic characteristics derived from published echocardiographic studies are shown in Table 1 [8,[10][11][12][15][16][17][18].…”
Section: Bioprosthesesmentioning
confidence: 99%